Anthropogenic pressure in a marine world: Distribution, movement, diet and parasite infestation of red-throated divers Gavia stellata in the context of habitat change - Kleinschmidt, Birgit (2022)
Information on the behaviour and ecology of seabirds provides an important basis for better understanding the effects of changes in their habitats and developing conservation strategies accordingly. The red-throated diver Gavia stellata breeds in Arctic regions and is found in coastal marine offshore areas outside the breeding season. German waters contain some important non-breeding areas for this species, with internationally relevant populations such as in the German Bight. Nevertheless, these areas are also characterized by high anthropogenic use, leading to strong responses in this species with avoidance distances of over 10 km and significant changes in distribution patterns. If these responses have long-term effects at the population level is still unclear due to the lack of basic studies on behavioural-ecological aspects. Therefore, this dissertation, aimed at filling the knowledge gapes related to dietary, migratory, and disease ecology. The cumulative dissertation presented here is structured into three chapters, each of which addresses a behavioural-ecological topic presented in chapters 1, 2, and 3, respectively. Specifically, the diet of red-throated divers in the German Bight was analysed using DNA-metabarcoding on sample sets from two consecutive years (Chapter 1). The results showed an opportunistic piscivorous prey spectrum which, however, included a high proportion of energetic rich species in both years, with clupeids as the most frequented prey items. These findings confirm other studies from e.g. the Baltic Sea. The continuous presence of high-energy prey fish in the diet helps to explain the importance of the German Bight due to the high availability of those fish species. Migratory behaviour and site use throughout the year, was studied using satellite telemetry and analysis of isotopic values from feather samples (Chapter 2). Breeding, moulting, and wintering sites were successfully determined of individuals inhabiting the German Bight. Migratory behaviour was characterized by regular ...